Mesenchymal Stem Cell Membrane-Coated TPCS2a-Loaded Nanoparticles for Breast Cancer Photodynamic Therapy - Greta Avancini; Luca Menilli; Adele Visentin; Celeste Milani; Francesca Mastrotto; Francesca Moret (MDPI AG, 2023)
Despite substantial improvements in breast cancer (BC) treatment there is still an urgent need to find alternative treatment options to improve the outcomes for patients with advanced-stage disease. Photodynamic therapy (PDT) is gaining a lot of attention as a BC therapeutic option because of its selectivity and low off-target effects. However, the hydrophobicity of photosensitizers (PSs) impairs their solubility and limits the circulation in the bloodstream, thus representing a major challenge. The use of polymeric nanoparticles (NPs) to encapsulate the PS may represent a valuable strategy to overcome these issues. Herein, we developed a novel biomimetic PDT nanoplatform (NPs) based on a polymeric core of poly(lactic-co-glycolic)acid (PLGA) loaded with the PS meso-tetraphenylchlorin disulfonate (TPCS2a). TPCS2a@NPs of 98.89 ± 18.56 nm with an encapsulation efficiency percentage (EE%) of 81.9 ± 7.92% were obtained and coated with mesenchymal stem cells-derived plasma membranes (mMSCs) (mMSC-TPCS2a@NPs, size of 139.31 ± 12.94 nm). The mMSC coating armed NPs with biomimetic features to impart long circulation times and tumor-homing capabilities. In vitro, biomimetic mMSC-TPCS2a@NPs showed a decrease in macrophage uptake of 54% to 70%, depending on the conditions applied, as compared to uncoated TPCS2a@NPs. Both NP formulations efficiently accumulated in MCF7 and MDA-MB-231 BC cells, while the uptake was significantly lower in normal breast epithelial MCF10A cells with respect to tumor cells. Moreover, encapsulation of TPCS2a in mMSC-TPCS2a@NPs effectively prevents its aggregation, ensuring efficient singlet oxygen (1O2) production after red light irradiation, which resulted in a considerable in vitro anticancer effect in both BC cell monolayers (IC50 < 0.15 µM) and three-dimensional spheroids.